2014
DOI: 10.1200/jco.2013.54.3926
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Methylprednisolone on Pain, Fatigue, and Appetite Loss in Patients With Advanced Cancer Using Opioids: A Randomized, Placebo-Controlled, Double-Blind Trial

Abstract: MP 32 mg daily did not provide additional analgesia in patients with cancer receiving opioids, but it improved fatigue, appetite loss, and patient satisfaction. Clinical benefit beyond a short-term effect must be examined in a future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(126 citation statements)
references
References 34 publications
5
119
1
1
Order By: Relevance
“…Of the three clusters identified by principal component analysis, we found significant improvement in the FAD cluster scores compared with placebo at day 8 and day 15 of treatment. Prior studies on the use of steroids showed short-term beneficial effects on cancer-related fatigue and anorexia [50][51][52]. However, no studies have investigated the use of steroids for the treatment of depression in advanced cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three clusters identified by principal component analysis, we found significant improvement in the FAD cluster scores compared with placebo at day 8 and day 15 of treatment. Prior studies on the use of steroids showed short-term beneficial effects on cancer-related fatigue and anorexia [50][51][52]. However, no studies have investigated the use of steroids for the treatment of depression in advanced cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…All of the 2443 patients who received opioids had poor systemic conditions, as indicated by baseline PPS 35 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The most common tumor type was respiratory tract tumor.…”
Section: Discussionmentioning
confidence: 99%
“…31) Concomitant use of antipsychotic, hypnotic, or antidepressant drugs may enhance central nervous system depressant effect and affect the respiratory function. Nevertheless, the current study demonstrated that opioid antagonists ameliorated respiratory depression in all cases, implying lesser effect of concomitant drugs on respiratory function.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether corticosteroids are effective in treating chemotherapy-related fatigue and/or malaise. During palliative care, the standard daily steroid dose for relieving fatigue is 2–8 mg of betamethasone and DEX, or 15–30 mg of prednisolone [6, 8, 9, 15-17]. Although some patients in this study might have approached the palliative care period, the use of higher doses (4–8 mg/day) of DEX is associated with the substantial possibility of AEs, which might adversely affect quality of life in the context of long-term cancer treatment.…”
Section: Discussionmentioning
confidence: 99%